Contexts of Loneliness in Women Choosing Voluntary Singlehood: A Qualitative Study in Mexico - Muñoz, Nayelli (Psychology of Woman Journal, 2025)
Objective: This study aimed to explore the emotional, sociocultural, and existential contexts of loneliness among women in Mexico who have consciously chosen voluntary singlehood. Methods and Materials: This research employed a qualitative exploratory design using semi-structured interviews to capture the lived experiences of women identifying as voluntarily single. A total of 22 participants aged between 27 and 49 years were recruited through purposive sampling from various regions in Mexico, including Mexico City, Guadalajara, Puebla, and Monterrey. Interviews were conducted in Spanish, recorded with consent, and transcribed verbatim. Data collection continued until theoretical saturation was reached. The data were analyzed using thematic analysis following Braun and Clarke’s framework, supported by NVivo 14 software for systematic coding and organization. Rigor was ensured through member checking, peer debriefing, and maintenance of an audit trail throughout the analysis process. Findings: Three overarching themes emerged: (1) Emotional Landscapes of Solitude, describing women’s redefinition of loneliness as reflective solitude balanced with emotional ambivalence; (2) Sociocultural Frames of Expectation, capturing the influence of cultural scripts, family pressure, and stigma in shaping the social experience of singlehood; and (3) Strategies of Meaning-Making and Self-Construction, reflecting participants’ agency in redefining fulfillment, establishing supportive social networks, and framing singlehood as a feminist and existential choice. Conclusion: Voluntary singlehood among women in Mexico represents a complex psychosocial process of self-definition within traditional cultural boundaries. Loneliness in this context is best understood not as deprivation but as an evolving emotional state rooted in agency, meaning-making, and resistance to normative gender expectations.